Mekanisme Pengambilan Keputusan Calon Mahasiswa melalui Ulasan Online: Peran Rute Sentral dan Rute Periferal - Soraya Asnusa; Herlina Herlina; Bandarsyah Bandarsyah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Online reviews are important information in promoting universities digitally to prospective students by using the concept of the Elaboration Likelihood Model (ELM) through the central route and the peripheral route to produce the desired goal, namely to analyze the extent to which online reviews influence prospective students' decisions in choosing and registering to a university, and to distinguish the mechanisms of influence based on the information processing path through these two routes. The method used is quantitative with a sampling technique using purposive sampling that has attributes that lead to the characteristics of the subject to obtain primary data through an online survey that will be distributed through a questionnaire using Google Forms, where the data obtained will be processed using Smart-PLS 4.0. The results obtained are an influence between the consistency of information on the decision to choose a university and there is an influence of source credibility on the decision to choose a university so that the formation of a central route from the results of the influence of information consistency on the decision to choose a university and a peripheral route is obtained from the influence of credibility on the decision to choose a university.